Highly Efficient Halide Perovskite Light‐Emitting Diodes via Molecular Passivation. Issue 15 (4th March 2021) - Liang, Aihui; Wang, Kang; Gao, Yao; Finkenauer, Blake P.; Zhu, Chenhui; Jin, Linrui; Huang, Libai; Dou, Letian
Abstract: Metal halide perovskites are promising for applications in light‐emitting diodes (LEDs), but still suffer from defects‐mediated nonradiative losses, which represent a major efficiency‐limiting factor in perovskite‐based LEDs (PeLEDs). Reported here is a strategy to synthesize molecular passivators with different anchoring groups for defects passivation. The passivated perovskite thin films exhibit improved optoelectronic properties as well as reduced grain size and surface roughness, thus enable highly efficient PeLEDs with an external quantum efficiency of 15.6 % using an imidazolium terminated passivator. Further demonstrated is that the in situ formation of low‐dimensional perovskite phase on the surface of three‐dimensional perovskite nanograins is responsible for surface defects passivation, which leads to significantly enhanced device performance. Our results provide new fundamental insights into the role of organic molecular passivators in boosting the performance of PeLEDs. Abstract : Organic molecular passivators with different terminal groups are synthesized, which can effectively passivate the surface defects of MAPbI3 ‐based films by forming mixed‐phase perovskite nanograins. Moreover, highly efficient PeLEDs with EQE of 15.6 % are achieved by utilizing an imidazolium terminated passivator. This work opens up a new opportunity of molecular engineering for the development of high‐performance PeLEDs.